2023
DOI: 10.3390/ijerph20054258
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Pyrethroids in the Malaria Vector Anopheles albimanus in Two Important Villages in the Soconusco Region of Chiapas, Mexico, 2022

Abstract: Chiapas State comprises the largest malaria foci from Mexico, and 57% of the autochthonous cases in 2021, all with Plasmodium vivax infections, were reported in this State. Southern Chiapas is at constant risk of cases imported due to migratory human flow. Since chemical control of vector mosquitoes is the main entomological action implemented for the prevention and control of vector-borne diseases, this work aimed to investigate the susceptibility of Anopheles albimanus to insecticides. To this end, mosquitoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…A recent publication from Solis-Santoyo et al reported An. albimanus populations that were resistant to deltamethrin and permethrin but susceptible to malathion and bendiocarb in two localities in Chiapas State in southern Mexico [ 32 ]. These results differ from the data presented here in two ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication from Solis-Santoyo et al reported An. albimanus populations that were resistant to deltamethrin and permethrin but susceptible to malathion and bendiocarb in two localities in Chiapas State in southern Mexico [ 32 ]. These results differ from the data presented here in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…First, the entomological collections in Chiapas were conducted in cattle corrals from localities with insecticide pressure derived from livestock and agriculture activities. Second, the diagnostic doses used in the bottle bioassays in the Chiapas study were established using a local reference strain, with insecticide concentrations lower than those recommended by globally recommended protocols [ 32 – 35 ]. National insecticide resistance data for malaria vectors is scarce, highlighting the importance of defining consistent methods for monitoring insecticide susceptibility of anophelines in Mexico.…”
Section: Discussionmentioning
confidence: 99%